Using of electron cyclotron resonance discharge in ion beam sputtering systems for space charge compensation - Bizyukov, A.A.; Tarasov, I.K.; Chibisov, A.D. (Вопросы атомной науки и техники, 2019)
The possibility of using a magnetic mirror in the output gap of ion source with a closed electron drift to generating of an additional gas discharge by using the electron-cyclotron resonance to compensate of the ion beam space charge is studied. The first experiments have shown that an additional microwave discharge generated in the region of the annular gap when the microwave power is applied. An additional plasma source of electrons provides the maintenance and intensification of the gas discharge in the accelerator with an anode layer. Вивчено можливість використання пастки пробочного типу у вихідному зазорі джерела іонів із замкнутим електронним дрейфом для генерації додаткового газового розряду з використанням електронно-циклотронного резонансу та компенсації просторового заряду іонного пучка. Перші експерименти показали, що генерується додатковий НВЧ-розряд в області кільцевого зазору при подачі НВЧ-потужності. Додаткове плазмове джерело електронів забезпечує підтримку та інтенсифікацію газового розряду в прискорювачі з анодним шаром. Изучена возможность использования ловушки пробочного типа в выходном зазоре источника ионов с замкнутым электронным дрейфом для генерации дополнительного газового разряда с использованием электронно-циклотронного резонанса и компенсации пространственного заряда ионного пучка. Первые эксперименты показали, что генерируется дополнительный СВЧ-разряд в области кольцевого зазора при подаче СВЧ-мощности. Дополнительный плазменный источник электронов обеспечивает поддержание и интенсификацию газового разряда в ускорителе с анодным слоем.